Productivity of berseem (trifolium alexandrinuum) sown alone and in combination with other fodder crops - Jahangeer, Arbab; Arshad, Muhammad; Musa, Muhammad; Muhammad, Noor; Munir, Kashif; Bazmi, Muhammad Sultan Ali (Journal of Pure and Applied Agriculture, 2023)
In Pakistan, berseem (Trifolium alexandrinum L.) is grown either alone or together with canola or sarson. Berseem has high protein content, but it is considered to have low dry matter content mostly in the first cut. Field experiments were conducted at Agronomy Section (Forage Production), Ayub Agricultural Research Institute, Faisalabad, Pakistan during 2019-20 and 2020- 21. The major objective of the experiment was to find out the best combination of fodder with berseem in order to get maximum green fodder yield with high protein content. Berseem was sown alone and in combination with oats, sarson, barley, haalun and ryegrass with different proportions by keeping “Super Berseem” as a base variety following RCBD with four replications. The crops were sown on 9th October 2019 and 12th October 2020. First cut was taken on 26th December during both years while subsequent cuts were taken on 15th February, 22nd March, 26th April during the year 2020, and 17th February, 25th March, 28th April during the year 2021. Results revealed maximum green fodder yield of 136.58 t ha-1 from plots where berseem 75% + oats 25% was sown, followed by berseem 75% + barley 25% was mixed (129.83 t ha-1 ). Maximum protein content (19.23%) was obtained where berseem alone was sown, followed by the treatment where berseem and ryegrass (18.40 %) were mixed. Mixed cropping of berseem 75 % + barley 25% produced the maximum crude fiber. It is recommended for farmers that berseem 75% + oats/barley 25% combination is more productive in quantitative terms, while qualitatively, berseem alone is the best option, particularly for mulching animals. © 2021 Department of Agricultural Sciences, AIOU